'Focus on diet quality': a qualitative study of clinicians' perspectives of use of the Mediterranean dietary pattern for non-alcoholic fatty liver disease. Issue 7 (14th October 2022) - Mayr, Hannah L.; Kelly, Jaimon T.; Macdonald, Graeme A.; Hickman, Ingrid J.
Abstract: Practice guidelines for non-alcoholic fatty liver disease (NAFLD) recommend promoting the Mediterranean dietary pattern (MDP) which is cardioprotective and may improve hepatic steatosis. This study aimed to explore multidisciplinary clinicians' perspectives on whether the MDP is recommended in routine management of NAFLD and barriers and facilitators to its implementation in a multi-ethnic setting. Semi-structured individual interviews were conducted with fourteen clinicians (seven doctors, three nurses, three dietitians and one exercise physiologist) routinely managing patients with NAFLD in metropolitan hospital outpatient clinics in Australia. Interviews were audio-recorded, transcribed and analysed using thematic content analysis. Clinicians described that lifestyle modification was their primary treatment for NAFLD and promoting diet was recognised as everyone's role, whereby doctors and nurses raise awareness and dietitians provide individualisation. The MDP was regarded as the most evidence-based diet choice currently and was frequently recommended in routine care. Facilitators to MDP implementation in practice were: improvement in diet quality as a parallel goal to weight loss; in-depth knowledge of the dietary pattern; access to patient education and monitoring resources and; service culture, including an interdisciplinary clinic goal, and knowledge sharing from expert dietitians. Barriers included perceived challenges for patients from diverse cultural and socio-economic backgrounds and limited clinician training, time and resourcing to support behaviour change. Integration of MDP in routine management of NAFLD in specialist clinics was facilitated by a focus on diet quality, knowledge sharing, belief in evidence and an interdisciplinary team. Innovations to service delivery could better support and empower patients to change dietary behaviour long-term.